Pengaruh Profitabilitas, Solvabilitas, dan Rasio Pasar Terhadap Capital Gain - Fitria Haeranisa; Sudjana (Indonesian Accounting Literacy Journal, 2022)
This study aims to analyze the effect of Return On Assets, Debt To Equity Ratio and Earning Per Share on stock returns listed on the Indonesia Stock Exchange in 2015-2019. This type of research is quantitative research using secondary data from financial reports from consumer goods companies listed on the Indonesia Stock Exchange in 2015-2019. In determining the sample is done by using purposive sampling. The number of samples in this study were 28 companies with a total of 85 observations that met the criteria for observation. This study uses two independent variables, namely Return On Assets (X1), Debt To Equity Ratio (X2) and Earning Per Share (X3) and one dependent variable, namely stock returns (Y). The data analysis technique used multiple linear regression analysis and statistical analysis was carried out with the help of IBM SPSS 25. The findings in this study, partially Return On Assets and Debt To Equity Ratio have a positive and significant effect on stock returns. While Earning Per Share has no significant effect on stock returns. Simultaneous testing shows that Return On Assets, Debt To Equity Ratio and Earning Per Share have a significant effect on stock returns.